PW 1040 Clinical presentation of traumatic brain injury victims: data from a tertiary-care hospital in kampala, uganda. (November 2018) - Mehmood, Amber; Zia, Nukhba; Ssenyonjo, Hussein; Kiryabwire, Joel; Hyder, Adnan A
Abstract : Clinical characteristics of traumatic brain injuries (TBIs) depend on severity of injury. The objective was to assesses clinical characteristics of TBI patients presenting to a tertiary-care hospital in Uganda. This prospective study was conducted at Mulago National Referral Hospital, Kampala, Uganda from May 2016-July 2017. Patients of all age groups presenting to emergency department (ED) of the Mulago Hospital with suspected or documented TBI were followed-up till discharge. Patient demographics, TBI characteristics, and outcomes were recorded. TBI was grouped into mild, moderate and severe categories based on Glasgow Coma Scale (GCS). Of the 3944 patients enrolled, 84.7% were males. Mean age was 28.5±14.2 years. Road traffic injury (58.9%) and assault (27.9%) were the common mechanisms. Headache (67.3%), scalp wound (65%) were common presenting complains. Most patients had closed TBI (62.9%). Common modes of arrival were police vehicle (33.9%), private vehicle (29%) and ambulance (26.8%). Alcohol use was suspected in 30.1% and drugs in 8.6% of the TBI patients at the time of initial presentation. Mean heart rate was 85.6±20.47 beats/minute, respiratory rate was 22.8±7.6/minute, systolic blood pressure was 120.0±18.6 mmHg. About 61.6% had mild TBI, 22.1% had moderate and 16.4% had severe TBI at the time of ED presentation. CT scan was done in 48.5% patients. 33.8% patients were sent home while 40% patients were admitted to wards. There were 109 deaths in the ED; 65 among mild TBI patients, 25 in moderate group and 19 in severe TBI group. Young male patients, with road traffic crash or assault are the most common victims of TBI. Majority patients had mild TBI but poor outcomes like ED death were observed within all categories of TBI patients. Understanding clinical parameters and causes of TBI patients is crucial to developing preventive strategies for prevention of TBI.